Three cases of liver toxicity with a dietary supplement intendedto stop hair loss - Julieta Fernández; Carmen Navascués; Gino Albines; Lissa Franco; María Pipa; Manuel Rodríguez (Revista Espanola de Enfermedades Digestivas, 2014)
Liver toxicity associated with herbal remedies and dietary supplements is an increasing concern. Several toxic hepatitis cases have been reported in the literature in association with products intended for weight loss where green tea extracts are an ingredient. Three hepatotoxicity cases are reported below in association with the use of Inneov masa capilar®, a dietary supplement intended to stop hair loss whose primary component is green tea catechins. In all of them, other potential causes of acute hepatitis were ruled out. We highlight the importance of awareness regarding these substances at history taking in order to identify and report hepatic adverse reactions secondary to apparently safe herbs as described in the present manuscript.